Age and Growth of Freshwater Drum and Gizzard Shad Occupying Two Reservoir‐River Complexes with Different Groundwater Contributions. (30th October 2019) - Dattilo, John; Shoup, Daniel E.; Brewer, Shannon K.
Abstract: Restoring groundwater flow is a management option that improves water temperature regimes and benefits fishes. Although this strategy applies more readily to river systems, the thermal character of reservoirs is heavily influenced by inflowing rivers. We examined differences in age, structure, and growth of both Freshwater Drum Aplodinotus grunniens and Gizzard Shad Dorosoma cepedianum that occupy catchments with varying groundwater contributions in the south‐central United States. Seepage run data indicated that the Kiamichi River was losing surface water to groundwater in summer 2016, whereas groundwater inflows were apparent in the Elk River basin. Summer 2016 data showed that the Elk River had cooler water temperatures than the Kiamichi River and Grand Lake O' the Cherokees water temperatures were similar to those in the incoming Elk River. We found higher densities of older Freshwater Drum and Gizzard Shad (maximums of 32 and 8 years old, respectively) in samples from the Grand basin than among fish that were sampled from the Kiamichi River basin (21 and 6 years old, respectively). Freshwater Drum grew at similar rates in both basins even though they reached larger maximum lengths in the Grand basin (649 mm TL) than in the Kiamichi River basin (600 mm). The average asymptotic length was greater for the Kiamichi population ( L ∞  = 613 mm) than for the Grand population ( L ∞  = 557 mm). Gizzard Shad from the Grand basin were larger than those from the Kiamichi River basin, though the latter population grew faster initially (Brody growth coefficient: K  =   0.787 versus K  =   0.179, respectively), but they had smaller asymptotic length ( L ∞  = 206 mm versus L ∞  = 343 mm). The role that groundwater plays in temperature regulation in these basins partially explains the observed differences. Our results suggest that the metabolic theory of ecology can be applied to fisheries management at a finer spatial scale.